DAMPAK DUALISME KEPENGURUSAN ORGANISASI PERHIMPUNAN ADVOKAT INDONESIA (PERADI) TERHADAP PENEGAKAN HUKUM - MASLON HUTABALIAN (JURNAL JUSTIQA, 2020)
In an effort to realize the principles of the rule of law in social and state life, the role and function of an advocate as a free, independent and responsible profession is important, in addition to the judiciary and law enforcement agencies such as the police and prosecutors. Through legal services provided, Advocates carry out their professional duties to uphold justice based on the law for the benefit of justice seekers, including efforts to empower people to realize their fundamental rights before the law. Advocates as one element of the justice system is one of the pillars in upholding the rule of law and human rights. The purpose of this study was conducted to explain the legal management of the Indonesian Advocates Association (PERADI) according to the Law, to find out how the dualism of the management of the Indonesian Advocates Association (PERADI) on law enforcement and society and how the role and efforts of the government to restore dualism management of the Association Indonesian Advocates (PERADI) became a single, strong organization.This study uses normative and empirical research methods which consist of research on legal observation and research on legal effectiveness. This study uses an interrelated concept of data collection through a qualitative approach and adjusted to applicable regulations.